2016
DOI: 10.1111/ajt.13911
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specificity of T Cell Infiltrates in Biopsies With T Cell–Mediated Rejection and BK Polyomavirus Viremia: Analysis by Next Generation Sequencing

Abstract: This study interrogates the antigen-specificity of inflammatory infiltrates in renal biopsies with BK polyomavirus (BKPyV) viremia (BKPyVM) with or without allograft nephropathy (BKPyVN). PBMC from 5 healthy HLA-A0101 subjects were stimulated by peptides derived from the BKPYV proteome or polymorphic regions of HLA. Next generation sequencing (NGS) of the T-cell receptor (TCR) cDNA was performed on peptide stimulated PBMC and 23 biopsies with T-cell mediated rejection (TCMR) or BKPyVN. Biopsies from patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…Resolving BKVAN often features SV40‐negative tubulointerstitial inflammation of plasma cells that persists despite viral clearance . TCR clonotype analysis of late biopsy samples demonstrates alloreactive cells admixed with larger numbers of noncognate T cells . Early cellular interstitial inflammation in our study was followed by IF/TA (independent of viral load), consistent with immune‐mediated damage amplifying the initial antiviral response.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Resolving BKVAN often features SV40‐negative tubulointerstitial inflammation of plasma cells that persists despite viral clearance . TCR clonotype analysis of late biopsy samples demonstrates alloreactive cells admixed with larger numbers of noncognate T cells . Early cellular interstitial inflammation in our study was followed by IF/TA (independent of viral load), consistent with immune‐mediated damage amplifying the initial antiviral response.…”
Section: Discussionsupporting
confidence: 57%
“…Viruses powerfully stimulate adaptive and innate immunity, and transcripts of cytotoxic T cell, macrophage, and natural killer cells are increased in viremic or BKVAN blood . Alloreactive TCR clonotypes that denote molecular rejection can appear in tissue after successful treatment . Our study found that substantial numbers of mononuclear cells persisted after sustained viral clearance in allografts that later failed from rejection.…”
Section: Discussionmentioning
confidence: 54%
“…Our material emphasizes once more the morphological overlap between PyVAN and the tubulointerstitial inflammation in acute TCMR . Despite progress with molecular analysis , it is not possible to categorically differentiate antiviral versus alloimmune T cell responses in biopsies with PyVAN . This issue is particularly significant, considering that worsening tubulitis in the second biopsy increased the risk of graft loss.…”
Section: Discussionmentioning
confidence: 96%
“…In other settings, minimization of immunosuppression during the initial period after transplantation, including MPA dose reduction and Tac dose reduction , has been shown to increase the risk of alloimmune response. In the specific context of BKV reactivation, the risk of dnDSAs emergence after drug minimization could be even more severe as it has been shown that the majority of graft infiltrating immune cells during BKVAN are alloreactive cells . In two previously published studies , the association between the emergence of dnDSAs (mainly class II) and immunosuppression reduction after BKV reactivation was also reported.…”
Section: Discussionmentioning
confidence: 99%